Jean-Louis Develly in Moscow: On the History of the Coronation Album of Empress Catherine II - Zhdanova, Anastasiia E. (Actual Problems of Theory and History of Art, 2023)
The drawings for the Coronation Album of Catherine the Great made between 1762 and the early 1770s by the French master J.-L. Develly (1730-1804(?)) in cooperation with the Russian artist M. I. Makhaev (1718–1770) are a unique monument of the graphic art of the 18th century. They have often been the subject of attention of Russian scholars, primarily M. A. Alekseeva and K. V. Malinovsky, who studied them in the context of the work of the Russian artist. However, the role of J.-L. Develly, who guided the process of creation of the drawings, cannot be diminished. The life and work of this French master, who worked in Russia from 1754 to 1804, has not been covered in detail in the academic literature. His work on the Coronation Album together with M. I. Makhaev is an important part of the artistic heritage of the master, whose contribution to the history of Russian art has not yet been fully explored. The goal of this study is to reconstruct the process of J.-L. Develly’s work on the Coronation Album using the surviving archival documents from the Russian State Historical Archive (RGIA) and the Russian State Archive of Ancient Documents (RGADA), including those which have not yet attracted the attention of researchers. A considerable part of the joint work of the Russian and French artists was carried out in Moscow, the traditional location of the coronation celebrations. A whole stratum of documents describing the various stages of production of the drawings has been preserved. They allow us to take a new look both at the process of the creation of the Coronation Album and at some aspects of the joint work of the two masters as an example of collaboration between the representatives of different artistic traditions.